Application of Principle Component Regression and Partial Least Square to the Simultaneous Kinetic-Spectrophotometric Determination of Ternary Mixture of Hydrazine, Phenylhydrazine and Acetylhydrazine - KARIMI, M.A.; TAHER, M.A.; BEHJATMANESH ARDAKANI, R.; ABDOLLAHZADEH, S. (Asian Journal of Chemistry, 2010)
A method for the simultaneous determination of the hydrazine (HZ) and its derivatives in water samples has been investigated and developed. It is based on reaction kinetics and spectrophotometry and results are interpreted with the aid of partial least squares regression (PLS) and principal component regression (PCR). The analytical method relies on the differential rates of reduction of copper(II) with HZ, phenylhydrazine (PHZ) and acetylhydrazine (AHZ) in the presence of neocuproine (NC) and monitoring the resulted coloured complex of Cu(I)/NC in sodium dodecyl sulfate (SDS) as micellar media at 452 nm. The optimized method was successfully tested by analyzing each of the species independently and linear calibration models are described. The results showed that simultaneous determination of HZ, PHZ and AHZ in ternary mixtures using these chemometrics methods could be performed in their concentration ranges of 0.10-1.0, 0.10-6.0 and 0.50-100 μg mL-1, respectively. The root mean squares errors of prediction (RMSEP) of HZ, PHZ and AHZ were 0.016, 0.026 and 0.054 (for PLS) 0.011, 0.095 and 0.141 (for PCR), respectively. Both the proposed methods (PCR and PLS) were validated using a set of synthetic sample mixtures and subsequently applied to the simultaneous determination of HZ, PHZ and AHZ in water samples.